Biosystematic Studies of some Species of the Tribe Cichorieae (Asteraceae) in Nigeria. - Adegbite, Emman Adegoke (Obafemi Awolowo University, 2014)
Five herbaceous species belonging to four genera of the tribe Cichorieae (Asteraceac) were characterised morphologically and cytologically. The species are Latuca capensis Thunb., Lactuca sativa Linn., Launaea taraxacifolia (Willd) Amin. ex C. Jeffrey, Picris humilis EC and Sonchus oleraceus Linn. The work is aimed at investigating the basis of intra-and inter-specific as well as intra-and inter-generic differences occurring among the species. It is envisaged that both the genetic and environmental components of the morphological differences among the species of the tribe could serve as a clue to the evolutionary relationship of the species. The plants and fruits (achenes) collected from different parts of Nigeria were transplanted or raised from achenes in the screen house to maturity. They were subjected to morphological, cytological (mitotic and meiotic), fertility (using pollen) and leaf anatomical studies. All the species with the exception of L. sativa (cultivated lettuce) are weeds. L. capensis, P. humilis and L. taraxacifolia are perennated by rootstocks and rhizomes, while L. sativa and S. oleraceus are annuals. The intra-specific and inter-specific variability of measured morphological attributes emphasises plastic responses to environmental conditions which characterizes weedy and colonizing species. The close resemblance between P.humilis and L. capensis, their ecological association and the general occurrence of characteristics that are diagnostic of the tribe in all the species suggest some genetic relationship and possibility of inter-generic and inter-specific hybridization among the species of the tribe. The persistence of intra-specific morphological differences in the species collected from different locations when raised under the same conditions implicates the genetic basis of some variations. Mitotic and meiotic chromosime studies corroborate previous observations on chromosome numbers for all the species. L. sativa, P. humilis and L. taraxacifolia have n=9 (2n=18) chromosomes, while L. capensis and S. oleraceus have n=8 (2n=16) and n=16 (2n=32) chromosomes respectively. Meiotic studies reveal normal formation of bivalents, though occasional multivalent associations at diplonema were recorded in L. sativa and L. taraxacifolia. From karyotype studies, the species were assigned karyotypic formulae which indicate numbers, size and centromere position of the chromosomes, L. capensis, 8Cnm; L. sativa, 3A nsm(-) + 3B nsm(-) =3Bnm: L. traxacifolia, 5bnm + 4Cnm; P. humilis, 1Anm + 8Bnm; and S. oleraceus, 2Cm + 14Cnm. The close genetic identity of the species can also be seen in the close pollen size, shape and sculpture. Occurrence of four germ pores on pollens of S. oleraceus underscores the probability that it is a polyloid. Pollen colour corresponds to the colour of the ligule, indicating that the same gene may condition both ligule colour and pollen colour. All the species showed high pollen fertility and anomocytic stomatal tyre.